THE SELECTION TECHNIQUE OF BULBIL PORANG (Amorphophallus muelleri Blume) BASED ON GROWTH RESPONSE - Qurrota A'yun (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Brawijaya, 2019)
Bulbil is a vegetative reproductive organ which is located on center and site of branching of porang leaf. The purpose of this study was to determine growth response between the center bulbil, the 1st- and 2nd- branch bulbils.All bulbils were obtained from 2 years old porang which has petiole with height 119.8 – 120 cm. All porang previously were cultivated in Rejosari Village, Bantur District. The harvested Bulbils were grown in a polybag (15x15 cm) which contain mixture of soil, manure, cocopeat and husk charcoal (5:3:1:1). The unit experiment where each types bulbilwas grown has 3 replications. Each replicate consisted of 15 plants. The experiment was organized by completely random designed. The ANOVA test was applied to all data. The result showed that differences in source the bulbil in term position(center bulbil, 1st- and 2nd- branch bulbils) significantly affected the time for appearance 1st shoot, germination rate and germination uniformity. The petiole height-diameter and the canopy width of porang plants were affected by source of bulbil as well. The best results for all parameter were given by seeded-bulbil derived from center bulbil. All the bulbils produce more than one shoots in one planted bulbil.DOI: http://dx.doi.org/10.21776/ub.jeest.2019.006.01.5